MiR‐125b‐1 and miR‐378a are predictive biomarkers for the efficacy of vaccine treatment against colorectal cancer. Issue 11 (22nd September 2017) - Tanaka, Hironori; Hazama, Shoichi; Iida, Michihisa; Tsunedomi, Ryouichi; Takenouchi, Hiroko; Nakajima, Masao; Tokumitsu, Yukio; Kanekiyo, Shinsuke; Shindo, Yoshitaro; Tomochika, Shinobu; Tokuhisa, Yoshihiro; Sakamoto, Kazuhiko; et al.
Abstract : Many clinical trials of peptide vaccines have been conducted. However, these vaccines have provided clinical benefits in only a small fraction of patients. The purpose of the present study was to explore microRNAs (miRNAs) as novel predictive biomarkers for the efficacy of vaccine treatment against colorectal cancer. First, we carried out microarray analysis of pretreatment cancer tissues in a phase I study, in which peptide vaccines alone were given. Candidate miRNAs were selected by comparison of the better prognosis group with the poorer prognosis group. Next, we conducted microarray analysis of cancer tissues in a phase II study, in which peptide vaccines combined with chemotherapy were given. Candidate miRNAs were further selected by a similar comparison of prognosis. Subsequently, we carried out reverse‐transcription PCR analysis of phase II cases, separating cancer tissues into cancer cells and stromal tissue using laser capture microdissection. Treatment effect in relation to overall survival (OS) and miRNA expression was analyzed. Three miRNA predictors were negatively associated with OS: miR‐125b‐1 in cancer cells ( P = 0.040), and miR‐378a in both cancer cells ( P = 0.009) and stromal cells ( P < 0.001). Multivariate analysis showed that expression of miR‐378a in stromal cells was the best among the three predictors (HR, 2.730; 95% CI, 1.027–7.585; P = 0.044). In conclusion, miR‐125b‐1 and miR‐378a expression might be considered as novel biomarkers to predict the efficacy of vaccine treatment against colorectal cancer. Abstract : This is the first study to report that miR‐125b‐1 and miR‐378a might be novel biomarkers to predict the efficacy of vaccine treatment against colorectal cancer. In the present study of peptide vaccine in combination with standard chemotherapy for metastatic colorectal cancer patients, we reported that three miRNAs were negatively associated with OS: miR‐125b‐1 in cancer cells ( P = 0.040), and miR‐378a in both cancer cells ( P = 0.009) and stromal cells ( P < 0.001).